The Effect of Yap Taz on Flexibility Exercise in Patient With Idiopathic Scoliosis - Yenni Limyati; Adelia Safira; Grace Puspasari (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTDuring the outbreak of Covid-19, the policy of working from home for employees and studying from home for students create a new problem. Employees and students mostly have to sit for long periods of time. This can affect body posture leading to lower back pain. Scoliosis is a postural disorder consistingof lateral curvature and rotation of the vertebrae. The etiology of idiopathic scoliosis remains unknown, and still present as theoretical hypothesis’s experts. One of non-surgical treatment that has been used for mild to moderate scoliosis is flexibility exercises. Flexibility exercises have been reported to reducethe degree of curvature in idiopathic scoliosis through the muscle hypertrophy mechanism. Muscle hypetrophy is regulated by Yes-associated protein (Yap) and transcriptional co-activator with PDZbinding motif protein (Taz) through three pathways, such as Hippo pathway signal, mechanosensorresponse, and mTOR signaling. The aim of this review is to examine more deeply the effect of Yap Taz protein on flexibility exercises in idiopathic scoliosis patien ts.Keywords: flexibility, hypertrophy, scoliosis, Taz, Yap.